Islamic digital economy and SME integration into global value chains: Evidence and policy implications for emerging economies - Setyono, Joko; Pambekti, Galuh Tri (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Small and medium-sized enterprises (SMEs) play a central role in global economic development, yet participation in global value chains (GVCs) remains constrained. This study examines how digitalization from an Islamic perspective, particularly through information and communication technologies (ICT), influences SME integration into GVCs while identifying structural barriers in developing economies. Drawing on a conceptual and analytical approach, the study synthesizes literature on digital adoption, SME internationalization, and GVC participation to develop an integrative framework linking Islamic digital capabilities with export performance and value chain integration. Findings indicate that ICT adoption, such as websites, e-commerce platforms, and digital logistics systems, enhances export capacity by reducing transaction costs, improving market access, and strengthening supply chain coordination. However, benefits remain uneven due to persistent constraints, including limited digital infrastructure, inadequate internet accessibility, and low levels of Islamic-oriented technological literacy. These barriers disproportionately affect SMEs in developing economies, reinforcing structural inequalities in GVC participation. The study contributes by integrating digitalization and GVC perspectives within an Islamic framework and highlights the need for policy interventions that strengthen infrastructure, enhance digital skills, and support inclusive ecosystems for sustainable SME participation